Ready, set, go! Profiling teachers' readiness for online teaching in secondary education. Issue 1 (1st January 2021) - Howard, Sarah K.; Tondeur, Jo; Siddiq, Fazilat; Scherer, Ronny
ABSTRACT: In a very short time, secondary school education across the globe transitioned to online learning and teaching, in response to the Covid-19 pandemic. This study aims at identifying teacher profiles in secondary education to better understand perceptions of both individual and institutional readiness to transition to online teaching. To do this, the current study grouped teachers on the basis of their TPACK self-efficacy beliefs, online presence and perceived institutional support for online teaching. To date, data have been collected from teachers ( N = 222) from 20 countries. The data were submitted to latent profile analysis to identify readiness profiles. The added value of the current study lies in the combined view of individual and institutional readiness and the uniqueness of the dataset. It provides a large-scale international perspective and a wide range of possible experiences. Findings inform how education institutions can personalise and support transitions to online teaching.